2023
DOI: 10.3390/tropicalmed8080379
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Durability as a Function of Fabric Strength and Residual Bio-Efficacy for the Olyset Plus and Interceptor G2 LLINs after 3 Years of Field Use in Tanzania

Salum Azizi,
Jackline Martin,
Njelembo J. Mbewe
et al.

Abstract: Long-lasting insecticidal nets (LLINs) are prone to reduction in insecticide content and physical strength due to repeated washes and usage. The significant loss to these features jeopardizes their protection against bites from malaria vectors. Insecticide washout is attributed to routine use, friction, and washing, while fabric damage is associated with routine use in households. To maintain coverage and cost-effectiveness, nets should maintain optimal bio-efficacy and physical strength for at least 3 years a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Testing the mosquitoes against new and 36 months-old chlorfenapyr-treated IG2 nets still indicates the efficacy of the insecticide against selected mosquito colonies ( Azizi et al, 2023 ). Our result is consistent with several study findings, where chlorfenapyr was found to be effective against pyrethroid-resistant mosquitoes ( Oxborough et al, 2015 ; NʼGuessan et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Testing the mosquitoes against new and 36 months-old chlorfenapyr-treated IG2 nets still indicates the efficacy of the insecticide against selected mosquito colonies ( Azizi et al, 2023 ). Our result is consistent with several study findings, where chlorfenapyr was found to be effective against pyrethroid-resistant mosquitoes ( Oxborough et al, 2015 ; NʼGuessan et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given their novelty and limited deployment to date, little durability monitoring data on multi-year field performance is published on dual AI ITNs [ 29 , 30 ]. The field performance of new net types under natural conditions was studied for 36 months after the 2019 mass campaign in Burkina Faso.…”
Section: Introductionmentioning
confidence: 99%